DIVIDEND POLICY AND MARKET VALUE OF NIGERIAN LISTED DEPOSIT MONEY BANKS - Oyewole Oladunni AJIBOYE; Yemisi F BOSUN-FAKUNLE; Johnson Kolawole OLOWOOKERE (Malete Journal of Accounting and Finance, 2024)
The two obvious choices involving amount the bank need for investments as well as for dividends distribution have been an issue. In most regulations, dividend payment had been withheld in order to satisfy investment decision as if it is not essential. Therefore, this study investigated dividend policy’s influence on listed Nigerian deposit money banks’ market value. An ex post facto research design was utilised while a purposive sampling approach was applied to select 12 banks out of the total population of 14 banks that were listed consistently with available data within the period of examination. Detailed information as regards market value (Tobin Q and share price) as well as dividend policy (dividend payout, dividend per share, dividend yield) of Nigerian listed banks was obtained from their annual reports together with accounts that were made public between 2011 and 2022 as well as Nigerian Exchange Group Fact Book, 2022. Data collected were analysed using descriptive (mean, median, standard deviation) and inferential statistics (correlation and panel data estimation). The outcomes reveal that dividend policy represented by dividend payout had positive and significant influence on the market value. This suggested that paying dividend regularly to the shareholders led to high market value. This study concluded that dividend policy influence market value of listed deposit money banks in Nigeria. It was recommended that bank management should pay attractive dividend regularly to their respective shareholder. Also, there should be regulation as to paying dividend regularly.